In Silico design of an H7N7 avian influenza vaccine with potential long-term applicability through the alteration of predicted immunodominant epitopes - Lapid, Carlo M.
Recent outbreaks of avian influenza in poultry and humans all throughout the world have raised concerns over the possibility of a global influenza pandemic. In 2003, there occurred a major outbreak of H7N7 avian influenza in the Netherlands, which affected millions of poultry and over a thousand humans. H7N7 has since been regarded as a potential pandemic threat. The objective of this study is the in silico design of a vaccine that promotes a broad immune response that can provide long-term immune protection. Immunodominant epitopes in the H7 protein sequence were identified by 3D window analysis of its physico-chemical properties, and verification of the identified epitopes was performed through other epitope prediction algorithms, consistency with data available in the literature, as well as structural analysis and sequence alignment. Finally, key residues in immunodominant epitopes were altered to reduce antigenicity, and thus promote an immune response against less antigenic sites. The resulting sequence can be the basis for a novel vaccine that can provide long-term immunity against H7 influenza subtypes, in spite of antigenic drift.